Islamic Social Fund (Zakah Infaq Shodaqoh), Inflation, and Poverty Alleviation in Surabaya City - Balqis, Nabilah (EkBis: Jurnal Ekonomi dan Bisnis, 2023)
This study analyzes the poverty rate in Surabaya in 2016-2020 which is supported by Islamic financial instruments and macroeconomic instruments. This study aims to examine the effect of receipt ZIS funds and inflation on the poverty rate in Surabaya in 2016-2020. This study used quantitative approach with multiple linear regression tests which were processed using the Eviews 10 program. The data used is time series data with the period of this study from January 2016 to December 2020. The data source was obtained from the East Java National Amil Zakat Agency (BAZNAS) and the Central Statistics (BPS) Surabaya City. The results of this study are indicating that the ZIS variable has a significant effect with a probability value of 0.0000 and has a negative direction with a coefficient value of -0.212219. This explains that the receipt of ZIS funds at BAZNAS East Java can reduce the number of poor people from 2016 to 2020. Meanwhile, the inflation variable has no significant effect on poverty with a probability value of 0.8062, and has a negative direction with a coefficient value of -0.006093. This happened because the inflation rate which was still fluctuating had no effect on the poverty rate in Surabaya from 2016 to 2020. Then simultaneously the ZIS variables and inflation together had an effect on the poverty rate in Surabaya in 2016-2020. While the results of the R2 test in this study indicate that the poverty rate in Surabaya is explained by the ZIS variable and inflation of 40.53% and the rest is explained by other variables outside the variables examined in this study.